Uji Biofungisida Pelet Berbahan Dasar Pelepah Kelapa Sawit Yang Mengandung Isolat Trichoderma spp. Terhadap Jamur Ganoderma boninense Pat. Secara In Vitro - Roy Ibrahim; Yetti Elfina; Rahmi Dewi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Basal stem rot (BSR) disease caused by Ganoderma spp.. The most of solution is using chemical pesticides and it was hazardous to environment and human health. The other way is using biological agent Trichoderma spp. in the form of biofungicide pellet. The aims of this research was to know the best influence of biofungicide pellet in controlling pathogen G. boninense of oil palm plant by in vitro. This research was done at Plant Pathology Laboratory of Agriculture Faculty and Nanotechnology Material Laboratory of Mathematics and Natural Science Faculty, University of Riau from May until July 2013. Experimental study was conducted using completly randomized design with 5 treatment and 4 replications. The treatment were application of biofungicide pellet is T0= Without isolate Trichoderma spp., T1= biofungicide pellet T. pseudokoningii, T2= biofungicide pellet T. koningii, T3= biofungicide pellet T. harzianum, T4= biofungicide pellet T. viride). Data obtained from the observations were statistically analyzed using analysis of variance, followed by Duncan's New Multiple Range Test (DNMRT). The result showed that biofungicide pellet containing isolate of Trichoderma spp. showing the different of patogen G. boninense by in vitro. Biofungicide pellet of T. harzianum has the higher result arround 58,84% and spores arround 16,47 x 106 than T. pseudokoningii, T. koningii and T. viride. Keyword: Palm Midrib, Isolat Trichoderma Spp, Mushrooms